2021
DOI: 10.12688/f1000research.28439.1
|View full text |Cite
|
Sign up to set email alerts
|

CFM: a database of experimentally validated protocols for chemical compound-based direct reprogramming and transdifferentiation

Abstract: Cell fate engineering technologies are critically important for basic and applied science, yet many protocols for direct cell conversions are still unstable, have a low yield and require improvement. There is an increasing need for a data aggregator containing a structured collection of protocols -  preprocessed, verified, and represented in a standardized manner to facilitate their comparison, and providing a platform for the researchers to evaluate and improve the protocols.   We developed CFM (cell fate mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For each small molecule, we represented a small molecule-induced transcriptome profile by a feature vector defined as , where p is the number of genes ( p = 978). Of these, 1486 small molecules were registered in KEGG ( Kanehisa et al 2009 ), and 36 small molecules were experimentally confirmed to induce DR ( Sizykh et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…For each small molecule, we represented a small molecule-induced transcriptome profile by a feature vector defined as , where p is the number of genes ( p = 978). Of these, 1486 small molecules were registered in KEGG ( Kanehisa et al 2009 ), and 36 small molecules were experimentally confirmed to induce DR ( Sizykh et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%